2017
DOI: 10.1108/jmh-09-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

The Hawthorne studies: an analysis of critical perspectives, 1936-1958

Abstract: Purpose The purpose of this paper was to analyse the academic context of the Hawthorne studies from 1936. More specifically, great attention was paid towards those articles that were critical of the Hawthorne studies. This study aimed to analyse why the Hawthorne studies were so criticized during the time period. Design/methodology/approach The author analysed various critical articles/books from the time period. The author developed the sample through the use of Landsberger’s Hawthorne Revisited. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…Mills and coauthors have demonstrated that the Hawthorne studies did not receive notice in the textbooks until after World War II. My own work (Muldoon 2012(Muldoon , 2017 has found that many of the articles, especially criticisms, did not occur until after 1946, with Bell's article in Commentary serving as a jumping point for criticism. The largest explanation for this occurrence was that the economic hardship of the depression limited the spread of the Hawthorne studies' message (Blum 1976.…”
Section: The Good Warmentioning
confidence: 99%
See 3 more Smart Citations
“…Mills and coauthors have demonstrated that the Hawthorne studies did not receive notice in the textbooks until after World War II. My own work (Muldoon 2012(Muldoon , 2017 has found that many of the articles, especially criticisms, did not occur until after 1946, with Bell's article in Commentary serving as a jumping point for criticism. The largest explanation for this occurrence was that the economic hardship of the depression limited the spread of the Hawthorne studies' message (Blum 1976.…”
Section: The Good Warmentioning
confidence: 99%
“…Scholars, including Ellen O'Connor (1999a, b), Bruce andNyland (2011), andRichard Gillespie (1991) have all argued that the Hawthorne studies were less science and more advocacy. Scholars have challenged Mayo's arguments over his opinions on unions, the originality of his ideas, and the roles of groups, attitudes, and social motivations in the workplace (Muldoon 2017). His most persistent and ablest critic, Bruce, pointed out that Mayo was more concerned with providing businessmen with the ammunition to fight off unions and coddling favors with the Rockefellers than true science.…”
Section: Mayo's "Findings"mentioning
confidence: 99%
See 2 more Smart Citations
“…Incentives and Contentment (1938) fell on stony ground from a scholarly sociological perspective. Notwithstanding the Tavistock’s creation in 1947, the focus of which was largely industrial, postwar British academic sociology was in a considerably weaker position than its American equivalent, even taking into account the relative size of each country (Calhoun, 2007; Muldoon, 2017; Steinmetz, 2005, 2007). As a former student of Mayo’s, George Homans, put it when he embarked on sociological studies in postwar Cambridge:It feels clear to me that sociology has a bad name in Britain but just what sort of bad name and why is not so obvious.…”
Section: The Eclipse Of the Rowntree Studies In Britain By The Hawthomentioning
confidence: 99%